2012
DOI: 10.1088/0022-3727/45/25/255002
|View full text |Cite
|
Sign up to set email alerts
|

Magnonic band gap design by the edge modulation of micro-sized waveguides

Abstract: The potential to control the number of the spin-wave band gaps of a magnonic crystal (MC) by variation of its geometry is investigated by numerical simulations. The magnonic crystal is represented by a micro-sized planar ferromagnetic waveguide with periodically variable width. By choosing a step-like or sinusoidal variation of the width, the magnonic crystal reveals multiple or single band gaps, respectively. This allows for additional degrees of freedom in the design of MCbased microwave filters and phase sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…• It was shown, by means of numerical simulations, that the nature of single or multiple band gaps is defined by choosing a sinusoidal or step-like variation of the width of the spin-wave waveguide, respectively [205]. This creates an additional degree of freedom in the control of magnonic crystal properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• It was shown, by means of numerical simulations, that the nature of single or multiple band gaps is defined by choosing a sinusoidal or step-like variation of the width of the spin-wave waveguide, respectively [205]. This creates an additional degree of freedom in the control of magnonic crystal properties.…”
Section: Discussionmentioning
confidence: 99%
“…The magnonic crystal was represented by a micro-sized planar ferromagnetic waveguide with periodically changing width. By choosing a step-like or sinusoidal variation of the width, the magnonic crystal revealed multiple or single band gaps, respectively [205]. In addition, it was found that both the band gap frequency and depth depend strongly on the probing position inside the magnonic crystal due to the non-uniform distribution of the internal magnetic field.…”
Section: Micro-structured Metallic Magnonic Crystals Based On the Permentioning
confidence: 99%
“…Nevertheless, few theoretical reports on the study of dispersion of SWs in 3D MCs have been made. 25,26 Structured magnonic waveguides [27][28][29] have recently attracted considerable attention due to their selective transmission of microwave bands in the micro-and nano-scales and their potential applications in on-chip microwave signal processing and communication. Magnetic antidots have emerged as an important system of MCs; and a thorough investigation of high frequency magnetization dynamics in them has been reported in the literature.…”
Section: Magnonicsmentioning
confidence: 99%
“…The point is that, in practice, the mod ulation of one parameter of a waveguiding structure is accompanied by a variation of several other parame ters of the system [14,18].…”
Section: Introductionmentioning
confidence: 91%